Indonesia's Bankruptcy Law Reform for Stronger Cross Border Creditors' Protection - Saputri, Theodora Pritadianing (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2023)
AbstractAlong with the increase in foreign investment in Indonesia, there is a growing awareness that the current Insolvency Law, i.e., Law No. 37 of 2004 regarding Bankruptcy and Suspension of Obligation for Payment of Debts dated October 18, 2004 may not be adequate to deal with bankruptcy risk associated with multinational corporations and transnational transaction, also known as cross border insolvency. This paper seeks to analyse legal framework for issues arising in cross border insolvency, such as, access to debtor’s offshore assets, creditor rights and jurisdiction of the court for the better Indonesia’s Bankruptcy Law. The author will use normative approach to find the answer. The analysis will begin with the legal framework for cross border insolvency under the UNCITRAL Model Law on Cross-Border Insolvency which deals with procedural issues in Cross-Border Insolvency. The UNCITRAL Model Law was designed to be promote legal certainty for trade and investment and will be suitable to attract investor to invest in a country adopting the UNCITRAL Model Law. It will be followed by a brief overview of Indonesia’s bankruptcy law, particularly on how Law No. 37/2004 deals with transnational issues. The analysis on some Indonesia’s insolvency proceedings involving foreign creditors, multinational corporations or offshore estate will then be considered in the following section. The author’s research demonstrates that Indonesia might not be ready yet to adopt UNCITRAL Model Law on Cross-Border Insolvency and shall focus to several fundamental issues including creditors’ rights and jurisdiction of the court over multinational corporations.AbstrakSeiring dengan meningkatnya investasi asing di Indonesia, terdapat kesadaran yang semakin besar bahwa Undang-Undang Kepailitan yang berlaku saat ini, yaitu Undang-undang No. 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang tanggal 18 Oktober 2004 mungkin tidak cukup untuk menangani permasalahan tersebut. dengan risiko kebangkrutan yang terkait dengan perusahaan multinasional dan transaksi transnasional, yang juga dikenal sebagai kebangkrutan lintas batas. Makalah ini berupaya menganalisis kerangka hukum atas permasalahan yang timbul dalam insolvensi lintas negara, seperti akses terhadap aset debitur di luar negeri, hak kreditur, dan yurisdiksi pengadilan demi perbaikan Undang-Undang Kepailitan di Indonesia. Penulis akan menggunakan pendekatan normatif untuk menemukan jawabannya. Analisis akan dimulai dengan kerangka hukum untuk insolvensi lintas negara berdasarkan Model Law on Cross-Border Insolvency UNCITRAL yang mengatur permasalahan prosedural dalam Cross-Border Insolvency. Model Hukum UNCITRAL dirancang untuk meningkatkan kepastian hukum perdagangan dan investasi dan cocok untuk menarik investor agar berinvestasi di negara yang mengadopsi Model Hukum UNCITRAL. Bagian ini akan dilanjutkan dengan tinjauan singkat mengenai undang-undang kepailitan di Indonesia, khususnya mengenai bagaimana UU No. 37/2004 menangani isu-isu transnasional. Analisis terhadap beberapa proses kepailitan di Indonesia yang melibatkan kreditor asing, perusahaan multinasional atau perusahaan luar negeri akan dibahas pada bagian berikut. Penelitian penulis menunjukkan bahwa Indonesia mungkin belum siap untuk mengadopsi Model Hukum UNCITRAL tentang Kepailitan Lintas Batas dan harus fokus pada beberapa isu mendasar termasuk hak-hak kreditor dan yurisdiksi pengadilan atas perusahaan multinasional.